"Count it all joy": black women's interventions in the abolitionist tradition. Issue 2 (4th March 2021) - Stewart, Lindsey
ABSTRACT: In her introduction to Narrative of the Life of Frederick Douglass, Angela Davis notes that the abolitionist tradition often harboured a "gendered framework" that defined "black freedom" in terms of the "suppression of black womanhood". As such, Davis charges us with the task of "develop[ing] a framework that foregrounds both the complexities of gendered violence under slavery and possible gendered strategies for freedom". In this paper, I engage in this task in two ways. First, I analyse key gendered aspects of the abolitionist tradition that erase black women's agency. One important implication of my argument is that the abolitionist tradition prioritizes physical resistance in how we define 'black freedom' and in narratives of black life. Second, I argue that black women have intervened in this tradition by broadening our sense of agency and extending the landscape of liberation. My primary example will be hoodoo practices that emphasize divine submission rather than resistance in the works of black women abolitionists, such as in S cenes of the Life of Harriet Tubman and The Memoir of Old Elizabeth, a Coloured Woman .